PERENCANAAN DAN KAJIAN TEKNIS SISTEM PERPIPAAN AIR BERSIH DI DESA KENDERAN-GIANYAR - Sukadana, I G. K. (Buletin Udayana Mengabdi; Vol 11 No 2 (2012): Jurnal Udayana Mengabdi, 2012)
Kenderan village consist of 900 family with 4500 human that distribute at 10 sub-village, have potensial land resources like water spring is very much. That water spring in this erly is not manage carefuly, so the water spring can be benafit resources for village community. Kenderant village community now is hanging drinking water from dvelopmen that the cost is very ekspensive for villager.any community leader from this village have ideas too build clean water sistem to manage by community self. Join with mechanical engineering team from udayana university for doing a studies. The program doing with survei and measuring location methods. Data collection method of monograf and tofograf from this village. Discustion method and visibel study economicly. From technical studi can result is this plan to build clean water system program in Kenderan village is visibel for realisation. The pipe recomendation is minimal PVC type AW.